Milk fat: opportunities, challenges and innovation. Issue 14 (27th July 2021) - Mohan, Maneesha S.; O'Callaghan, Tom F.; Kelly, Phil; Hogan, Sean A.
Abstract: Milk fat is a high-value milk component that is processed mainly as butter, cheese, cream and whole milk powder. It is projected that approximately 35 million tonnes of milk fat will be produced globally by 2025. This surplus, enhances the need for diversification of milk fat products and the milk pool in general. Infant milk formula producers, for instance, have incorporated enzyme modified ("humanised") milk fat and fat globule phospholipids to better mimic human milk fat structures. Minor components like mono- and di-glycerides from milk fat are increasingly utilized as emulsifiers, replacing palm esters in premium-priced food products. This review examines the chemistry of milk fat and the technologies employed for its modification, fractionation and enrichment. Emerging processing technologies such as ultrasound, high pressure processing, supercritical fluid extraction and fractionation, can be employed to improve the nutritional and functional attributes of milk fat. The potential of recent developments in biological intervention, through dietary manipulation of milk fatty acid profiles in cattle also offers significant promise. Finally, this review provides evidence to help redress the imbalance in reported associations between milk fat consumption and human health, and elucidates the health benefits associated with consumption of milk fat and dairy products.